2011
DOI: 10.1177/0885328211432487
|View full text |Cite
|
Sign up to set email alerts
|

Positive charge of chitosan retards blood coagulation on chitosan films

Abstract: In this study, a series of chitosan films with different protonation degrees were prepared by deacidification with NaOH aqueous or ethanol solutions. The films were then used as a model to investigate the effects of the positive charge of chitosan on blood coagulation. The results showed that the positive charge of chitosan acted as a double-edged sword, in that it promoted erythrocyte adhesion, fibrinogen adsorption, and platelet adhesion and activation, but inhibited activation of the contact system. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 58 publications
2
58
0
Order By: Relevance
“…Regarding the aminated (positively charged) L‐PPE:N coatings, coagulation was also observed to be delayed; these cationic surfaces promote fibrinogen absorption, but inhibit the intrinsic pathway because thrombin generation is retarded . Moreover, L‐PPE:N presented the lowest degree of reproducibility and the slowest clot kinetics (highest K value, 12.4 min, see Figure ).…”
Section: Discussionmentioning
confidence: 98%
“…Regarding the aminated (positively charged) L‐PPE:N coatings, coagulation was also observed to be delayed; these cationic surfaces promote fibrinogen absorption, but inhibit the intrinsic pathway because thrombin generation is retarded . Moreover, L‐PPE:N presented the lowest degree of reproducibility and the slowest clot kinetics (highest K value, 12.4 min, see Figure ).…”
Section: Discussionmentioning
confidence: 98%
“…The GC nanogel was found to be non-haemolytic, and may also be considered non-thrombogenic, in agreement with He et al, who have found that the positive charge of chitosan retarded thrombin generation and blood coagulation. (He et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This pathway includes the coagulation factors XII (FXII), coagulation factors XI (FXI), high-molecular-weight-kininogen (HMWK), and pre-kallikrein. Contact of blood with functional biomaterials may produce two biological processes, including platelet adhesion and contact system activation, which have a strong synergistic effect on biomaterial-induced blood coagulation (Figure 1) [21]. Studies showed that CS induced blood coagulation in vitro was independent of coagulation factors VII (FVII) but required FXI and FXII [22].…”
Section: Hemostatic Mechanisms Of Chitosan (Cs)mentioning
confidence: 99%
“…Yunnan Baiyao , a well-known herb prescription used in oriental countries for more than 100 years, is an effective surgical sealant and hemostat. However, it is not suitable for direct intraluminal application due to the lack of an ideal substrate [21,65,66]. Lu et al [29] prepared chitosan/sodium alginate- Yunnan Baiyao composite hemostatic films by blending Yunnan Baiyao with CS and sodium alginate.…”
Section: Cs-based Composite Hemostatic Materialsmentioning
confidence: 99%